Highly sensitive analysis of organometallic compounds based on molecularly imprinted electrochemical sensors. Issue 11 (2nd March 2017) - Wei, Xiaoping; Wu, Ting; Yuan, Yali; Ma, Xionghui; Li, Jianping
Abstract : A highly sensitive molecularly imprinted electrochemical sensor constructed by a novel microporous metal–organic-framework for the detection of organometallic compounds was developed. Abstract : A highly sensitive molecularly imprinted electrochemical sensor constructed by a novel microporous metal–organic-framework for the detection of organometallic compounds was developed. A monolayer of 4-aminothiophenol (4-ATP) was self-assembled on the surface of a gold electrode, followed by electropolymerization of the 4-ATP-functionalized gold nanoparticles (Au NPs) in the presence of template molecules (thimerosal), forming a microporous molecularly imprinted polymeric (MOF-MIP) film. The obtained MOF-MIP film was characterized by cyclic voltammetry (CV), alternating current impedance spectroscopy, and scanning electron microscopy (SEM), exhibiting a higher specific surface area, faster rate of electron conduction, and more accessible imprinted molecular cavities compared with the MIP film prepared without Au NPs. Therefore, the MOF-MIP electrochemical sensor exhibited a significantly enhanced sensitivity. Thimerosal was determined in the range of 0.8–80 pM with the detection limit of 0.035 pM. The sensor was successfully applied to determine the amount of thimerosal in chloramphenicol eye drop samples, giving rise to further applications in the food industry and environmental field.